EGIDO GÁLVEZ, I.; MARTÍNEZ-USARRALDE, M.J. (2019). La educación comparada hoy. Madrid: Síntesis, 252 páginas, ISBN 978-84-9171-412-5 - L. Belén Espejo Villar (Universidad de La Rioja, 2020)
EGIDO GÁLVEZ, I.; MARTÍNEZ-USARRALDE, M.J. (2019). La educación comparada hoy. Madrid: Síntesis, 252 páginas, ISBN 978-84-9171-412-5.